Determination of Energy and Protein Requirements of Sheep in Indonesia using a Meta-analytical Approach - A. Jayanegara; M. Ridla; D. A. Astuti; K. G. Wiryawan; E. B. Laconi; Nahrowi Nahrowi (Faculty of Animal Science, Bogor Agricultural University, 2017)
The objective of this study was to determine energy and protein requirements, for both maintenance and gain, of sheep in Indonesia by using a meta-analysis method. A database was developed from various in vivo experiments involving sheep as the experimental animals in which energy intake, protein intake and average daily weight gain (ADG) were reported. A total of 38 articles consisting of 137 data points were integrated into the database. Different breeds (Priangan, fat-tailed and local) and sexes (male and female) were specified in the database. Maintenance and gain requirements of dry matter, energy and protein were determined by regressing ADG with dry matter intake (DMI), total digestible nutrient intake (TDNI) and crude protein intake (CPI), respectively. An intercept (where ADG= 0 g/kg MBW/d) and a slope (required nutrient intake per unit ADG) were taken as maintenance and gain requirements, respectively. Results revealed that all sheep breeds had similar energy requirement for maintenance (TDNm). Energy requirement for gain (TDNg) of Priangan breed was lower than other breeds; the breed required 0.860 g TDN for 1 g ADG. Fat-tailed and local breeds required 1.22 and 2.75 g TDN for 1 g ADG, respectively. All breeds also revealed relatively similar protein requirement for maintenance (CPm), i.e. 6.27-6.47 g/kg MBW/d. Priangan breed required less CP for 1 g ADG (CPg), i.e. 0.295 g. Requirements of CPg for fat-tailed and local breeds were 0.336 and 0.497 g/g ADG, respectively. It was concluded that each sheep breed in Indonesia had specific TDN and CP requirements for gain, but similar requirements for maintenance.